2007
DOI: 10.1300/j135v04n03_07
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Frustration and Aggressive Behaviors

Abstract: This study, conducted in a large public agency and a large private transportation company in the U.S., found strong relationships between organizational characteristics and frustration. Role ambiguity, role conflict, work constraints, and warmth and support predicted the level of frustration experienced by employees. In turn, frustration predicted supervisor-and self-reported aggression. Frustration also predicted self-reported criterion behaviors such as withdrawal, aggression turned inward, and abandonment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…Specifically, to the extent that employees felt a lack of control over their work situation (external WLOC), the more likely they were to engage in CWB. This is in line with previous findings regarding general LOC (e.g., Heacox, 1996; Perlow & Latham, 1993) and WLOC (e.g., Fox & Spector, 1999) as they relate to CWB. This also provides support for Wallhagen et als' (1994) assertion that externals tend to engage in less adaptive behaviors than internals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, to the extent that employees felt a lack of control over their work situation (external WLOC), the more likely they were to engage in CWB. This is in line with previous findings regarding general LOC (e.g., Heacox, 1996; Perlow & Latham, 1993) and WLOC (e.g., Fox & Spector, 1999) as they relate to CWB. This also provides support for Wallhagen et als' (1994) assertion that externals tend to engage in less adaptive behaviors than internals.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Fox and Spector (1999) demonstrated that an external WLOC was positively associated with both experienced frustration and CWB (i.e., work frustration–aggression model). In addition, general LOC has been found to be linked to aggression against others (Heacox, 1996) and client abuse among direct-care workers (Perlow & Latham, 1993). In each of these studies, externals demonstrated greater levels of CWB than internals.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…For instance, at the organizational level, obstacles to innovation include entrenched policies, procedures, and an adherence to the status quo (Amabile et al, 1996). In Dougherty and Hardy's (1996) study on problems with sustained product innovation, respondents expressed their frustration with management and with difficulty obtaining resources within the organizational political structure, Organizational frustration encompasses situational impediments that block goals and performance (Heacox and Sorenson, 2004;Spector, 1978).…”
Section: Innovation and The Firmmentioning
confidence: 99%
“…Organizations by their very nature produce frustration (Spector, 1978). The basic idea of organizational frustration is twofold: one is that there are organizational or situational factors associated with constraint that contribute to individual frustration with the organization and, two, that individual reaction to frustration can take the form of withdrawal behavior, altered task performance, and abandonment of goal (Heacox and Sorenson, 2004). Besides task performance, the work on frustration has been concerned with aggression (Spector, 1978;Storms and Spector, 1987).…”
Section: Organizational Frustrationmentioning
confidence: 99%
See 1 more Smart Citation